2002
DOI: 10.1046/j.1460-9568.2002.02033.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of local raised subplasmalemmal calcium concentrations in growth cones advancing on an N‐cadherin substrate

Abstract: We have used the membrane-localized calcium probe fura-piperazine-C12H25 (FFP-18) to examine cytosolic calcium concentrations in a volume close to the plasmalemma. Although promotion of axon outgrowth by cell adhesion molecules requires extracellular calcium and is correlated with an opening of plasmalemmal channels, conventional indicators cannot detect a change in the calcium concentration in such stimulated growth cones. We have examined calcium signalling in chick retinal ganglion cell growth cones extendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
(72 reference statements)
0
15
0
Order By: Relevance
“…CaMKI and the regulation of growth cone motility Transient increases of Ca 2ϩ that are spatially restricted within the growth cone can rapidly alter its morphology and motility, presumably by regulating actin dynamics (Lau et al, 1999;Zheng, 2000;Chadborn et al, 2002;Cheng et al, 2002;Meyer and Feldman, 2002). Our results indicate that CaMKK via its downstream target CaMKI mediates these effects on axonal growth cone motility.…”
Section: The Roles Of Camkii and Camkiv In Neurite Developmentmentioning
confidence: 68%
“…CaMKI and the regulation of growth cone motility Transient increases of Ca 2ϩ that are spatially restricted within the growth cone can rapidly alter its morphology and motility, presumably by regulating actin dynamics (Lau et al, 1999;Zheng, 2000;Chadborn et al, 2002;Cheng et al, 2002;Meyer and Feldman, 2002). Our results indicate that CaMKK via its downstream target CaMKI mediates these effects on axonal growth cone motility.…”
Section: The Roles Of Camkii and Camkiv In Neurite Developmentmentioning
confidence: 68%
“…Wherever gradients of Ca 2+ and redox exist local elevations and signaling should also. The plasma membrane divides a high Ca 2+ and oxidized cell exterior from the low Ca 2+ and reducing cytosol, as such Ca 2+ entry drives local elevations in neuronal models [101] which may be detected with probes anchored to the membrane but not the diffuse cytosol [102]. Local elevations of Ca 2+ restricted to the nm range below the plasma membrane have been shown to modulate neighboring plasma membrane Ca 2+ pumps [103] which are further regulated by local mitochondria [104].…”
Section: The Er-mitochondrial Interface: a Potential Stage For Locmentioning
confidence: 99%
“…Increased steady state levels of intracellular Ca 2+ were also recorded in growth cones of chick retinal ganglion cells grown on N-cadherin and loaded with a membrane targeted Ca 2+ indicator, FFP-18AM [40]. Interestingly, when the Fura-2AM reporter was used, steady state levels of intracellular Ca 2+ were found to be not affected by substrate coated recombinant N-cadherin suggesting that N-cadherin influences predominantly submembrane Ca 2+ levels [40].…”
Section: Reviewmentioning
confidence: 99%
“…Increased steady state levels of intracellular Ca 2+ were also recorded in growth cones of chick retinal ganglion cells grown on N-cadherin and loaded with a membrane targeted Ca 2+ indicator, FFP-18AM [40]. Interestingly, when the Fura-2AM reporter was used, steady state levels of intracellular Ca 2+ were found to be not affected by substrate coated recombinant N-cadherin suggesting that N-cadherin influences predominantly submembrane Ca 2+ levels [40]. Whole cell voltage clamp recordings also showed that homophilic binding of N-cadherin on neuronal membranes to soluble N-cadherin or N-cadherin overexpressed in Chinese hamster ovary (CHO) cells increases amplitudes of Ca 2+ currents in ciliary ganglion neurons indicating that homophilic interactions of N-cadherin are sufficient to activate a cellular mechanism that regulates Ca 2+ influx [41].…”
Section: Reviewmentioning
confidence: 99%